Prevalence of Aspergillus fumigatus complex in waste sorting and incineration plants: an occupational threat - Viegas, Carla (2016)
Aspergillus fumigatus is one of the major ubiquitous saprophytic fungi and it is considered one of the fungal species with higher clinical relevance. This study aimed at characterising the prevalence of A. fumigatus complex in one waste-sorting plant and also in one incineration plant. Conventional and molecular methodologies were applied in order to detect its presence. Aspergillus fumigatus complex was the second most frequently found in the air from the waste-sorting plant (16.0%) and from the incineration plant (18.0%). Regarding surfaces, it ranked the third species most frequently found in the waste-sorting plant (13.8%) and the second in the incineration plant (22.3%). In the waste-sorting plant, it was possible to amplify by qPCR DNA from the A. fumigatus complex in all culture-positive sampling sites plus one other sampling site that was negative by culture analysis. Considering the observed fungal load, it is recommended to apply preventive and protective measures in order to avoid or minimise worker's exposure.